New Substituted Mono-and Bis(imidazolyl)pyridines and their Application in Nitroaldolisation Reaction - Drabina, Pavel; Keder, Roman; Hanusek, Jiří; Sedlák, Miloš (Springer Verlag, 2006)
New chiral nitrogen ligands based on the substituted mono- and bis(imidazolyl)pyridines have been prepared and characterised. Their complexes with cupric acetate were used as catalysts in the nitroaldolisation reaction. In the case of optically pure complexes of mono(imidazolyl)pyridine, the isolated products were 2-nitro-1-(2-nitrophenyl)ethanols or 2-nitro-1-(4-nitrophenyl)ethanols in overall yields of 49-93 % and with the maximum enantiomeric excess of 15.6 %. The complexes of bis(imidazolyl)pyridine also catalyse the nitroaldol reaction, the yields being 64-90 %, but with zero enantioselective excess.
Keywords: imidazolylpyridines; catalysis; copper complex; aldolisation reaction